PERAN KERJA SAMA GURU DAN ORANG TUA TERHADAP PEMBINAAN AKHLAK PESERTA DI SMPIT TAHFIDZ NURUL ISLAM BATAM - Nyak Fadhillah Awaludina; Azmi Yuana; Nilna Nariatul Auliyah; Nailul Muna Salsabila Masrum; Hikmahtul Aisyah; Nurul Rahman; Sabrun Jamil (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study addresses the issue of varying levels of students’ moral conduct in school settings, despite the strong emphasis on character and religious development at SMPIT Tahfidz Nurul Islam Batam. The study aims to examine the forms of teacher parent collaboration and to assess its role in fostering students’ moral character (akhlak). A mixed-methods approach with an explanatory sequential design was employed: the first phase used questionnaires to measure the level of teacher parent collaboration and students’ moral character, followed by interviews and document review in the second phase to elaborate the quantitative results. Quantitative data were analyzed using descriptive and inferential techniques (relationship/effect testing), while qualitative data were analyzed thematically. The findings indicate that teacher parent collaboration plays a positive role in strengthening students’ moral character. The most supportive practices include regular communication (offline and online), monitoring worship routines and daily habits, consistent discipline agreements between home and school, and parenting programs. Key challenges involve parents’ limited time and inconsistent follow-up. Overall, the results highlight the need for structured communication mechanisms and shared commitment to ensure sustainable moral development. Keywords: teacher and parent collaboration, moral character development, Islamic junior high school (SMPIT Tahfidz)